Unleashing Central America’s Growth Potential : Nicaragua - Ulku, Hulya; Zaourak, Gabriel (World Bank, Washington, DC, 2021)
As the smallest economy in Central America, Nicaragua has undergone a structural transformation that has enabled the country to grow at a high pace since the mid-1990s. The objective of this study is to investigate the drivers and constraints of growth and productivity in Nicaragua and explore areas with high potential. The value added of this study is to provide an in-depth analysis of the drivers and constraints of Nicaragua’s growth using a wide range of analytical tools. Using these tools, the report finds that boosting growth and reducing poverty requires raising productivity growth and facilitating the entry of women to the labor market. According to the growth diagnostics methodology, this report finds that the areas preventing faster growth are: (i) corruption, (ii) financial development, (iii) governance, (iv) lack of innovation, and (v) property rights. Addressing the identified growth constraints can help the country in the path towards diversification, which will increase the resilience to external shocks, create job opportunities, generate sustainable growth, and reduce dependence on remittances. This report has identified several key areas where policy reforms can help boost productivity and growth over the medium to long term. They include: implementing measures to boost female labor force participation; increasing the access of small firms to finance and addressing collateral laws, credit information coverage, and competition; coordinate with the private sector to identify missing public goods and to design mechanisms to provide them; creation of an enabling environment for innovation; strengthening public institutions through reducing bureaucracy, promoting transparency and rule of law, and strengthening the capacity of the public sector; improving the property titling regime and the land administration system; and strengthening the institutional framework, including tackling corruption.